Microbiological and Nutritional Quality of Freshly Laid Emu Eggs Collected from Different Farms Located in Thane District Of Maharashtra Thane District Of Maharashtra - Zende, R. J.; Chavhan, D. M.; Rai, A. K.; Vaidya, V. M.; Save, H. V. (Journal of Meat Science, 2019)
A total of 60 freshly laid emu eggs were collected from six different emu farms located in Thane district of Maharashtra state. The eggs were analyzed for enumeration of Total Viable Count (TVC) and differential count and for determination of nutritional quality. The microbiological analysis of eggs revealed that average TVC (log cfu/ml) of emu eggs collected from Farm A, B, C, D, E and F were 2.68±0.56, 2.73±0.42, 2.92±0.36, 2.90±0.31, 2.91±0.41 and 2.95±0.44 while yeast and moulds counts were 1.44±0.22, 1.37±0.27, 1.62±0.15, 1.61±0.25, 1.45±0.18 and 1.68±0.17, respectively. Average S. aureus count (log cfu/ml) in emu eggs procured from Farm A, B, C, D, E and F observed were 1.72±0.10, 1.75±0.15, 1.54±0.38, 1.92±0.27, 1.88±0.20 and 1.84±0.10, respectively. However, E. coli and Salmonella spp. were not detected in any of the samples analyzed. The proximate analysis i.e. percent moisture, fat, protein, and ash content of emu egg samples from all the emu farms were in the range of 65.99±3.32 to 67.96±2.74, 14.99±0.78 to 16.28±0.79, 11.27±0.82 to 12.07±0.89, 1.40±0.30 to 1.76±0.57, respectively. Thus, it is concluded that the emu eggs collected from all the six different farms were nutritionally adequate and microbiologically safe for human consumption.